100 ways to save tax in Malaysia for small businesses - Thornton, Richard (Accountant) (Sweet & Maxwell Asia, 2010)
[This book] is designed specifically to help the owners of small businesses to learn and understand some of the important aspects of tax that bear directly on their situation.